Proposal of a structured methodology for the measure of intangible criteria and for decision making. (1st January 2014) - De Felice, Fabio; Petrillo, Antonella
Making decisions requires judgement. Judgement depends on feelings and thoughts and on the ability to interpret the information from the feelings and thoughts which arise from things happening that are inherently tacit, into attributes with different levels of intensity of preference, of importance, or of likelihood. This paper places special emphasis on the measurement of intangible criteria and on their incorporation into the resource allocation process through a proper decision making approach. In this paper, a well-known decision-making method, the analytic hierarchy process (AHP) is applied to identify a quality model to evaluate Italian racecourses' performances. The aim of the work is to provide a contribution to better understand the decision process of Italian racecourses because it is characterised by a decision process that is not well structured.